Attenuation Relationships for the Horizontal Component of Peak Ground Acceleration (PGAH) Using Gene Expression Programing (GEP) and Group Method of Data Handling (GMDH) - Mehrasa Ajam; Mohammad Shamekhi Amiri; Hossein Pahlavan (Advances in Civil Engineering)
Earthquake is one of the natural disasters that has always influenced human life. It is not currently possible to predict exactly when and where an earthquake will occur, nor how large it will be. It is also impossible to prevent an earthquake. However, by designing seismic-resistant structures, the amount of financial losses and casualties can be reduced. This resistant design requires the use of earthquake risk analysis. By using the earthquake risk analysis, it will be possible to estimate the parameters of the strong ground motion, including acceleration, velocity, and displacement in each area. Estimating the parameters of strong ground motion will be possible just by obtaining the appropriate attenuation relationship. The aim of this paper is to present an appropriate attenuation relationship to estimate the horizontal component of the possible occurrence of peak ground acceleration in each region. Two methods were used to calculate attenuation relationship: gene expression programing (GEP) and group method of data handling (GMDH). In the first step, an up-to-date and comprehensive catalog consisting of 1,185 earthquake records that occurred around the world has been prepared. In the next step, the parameters of magnitude, hypocentral distance, and shear wave velocity of these records have been used as variables of the attenuation relationship. Then, the fitness function (f) was determined, and attenuation relationships were calculated using GEP and GMDH. The amount of fitness function (f) was obtained 766.12 from 1,000 in the GEP method and 767.77 from 1,000 in the GMDH method. The values of the fitness function, residuals and comparison plots showed a high-agreement between “the values predicted by the attenuation relationships” and “the actual values observed in the earthquakes.” Finally, according to the results of this research, it can be said that the use of GEP and GMDH methods has provided better results than the other similar researches. Also, the use of up-to-date records makes the results of this research more reliable than the previous researches.